Subcutaneous zygomycosis in horses - Santos, Murilo Nogueira dos (2014)
Biopsied specimens from tumor masses of subcutaneous tissue of ten horses were examined. New sections were prepared and stained for fungi. Broad, non-septate hyphae of zygomycetes were found in the necrotic focci of the granulomatous tissue in four specimens. In view of the localization of the tumor, it was assumed that Hyphomyces destruens would have been the agent.